Description Of Community Knowledge And Attitude On Clean Water Sanitation In Flood Prone Areas On Pasar V Tembung Street Percut Sei Tuan District Deli Serdang District - Sylva Qamara Nur Fadilah; Rizqa Auliyah Shifah Sagala; Zahwatul Hasanah Siregar; Mega Rahmadani Siregar; Muhammad Ridwan; Putra Apriadi Siregar (Lembaga Pengembangan Kinerja Dosen, 2023)
Indonesia is a disaster-prone area. One of the most common disasters is flooding. Water is one of the important components for human survival. Water has a direct impact on human health. Flood-prone areas are at risk of carrying a disease called water bone disease, especially environmental-based diseases such as diarrhea. The importance of community knowledge and attitudes towards clean water sanitation can reduce the risk of flooding. The purpose of this study was to describe the knowledge and attitudes of the community towards clean water sanitation in flood-prone areas on Pasar V Medan Tembung Street, Percut Sei Tuan District, Deli Serdang Regency. This research was conducted on May 25 2023, 12.30 WIB until finished. This research is a quantitative research with a descriptive research type. Data collection was carried out by interviews and questionnaires. The results showed that 100% of the data obtained from 10 respondents stated that their home environment was prone to flooding which disrupted the quality of clean water from each respondent's house which was prone to flooding, then 10% of the water quality was poor and polluted during floods and 30% of respondents said the water supply was unstable during floods , and 40% of respondents said they experienced diarrhea during floods and 20% of respondents said they experienced itching during floods. The conclusion of this study is that the area prone to flooding on the Tembung V market road, Percut sub-district, Sei Tuan, Deli Serdang district greatly affects the quality of clean water around the place.